A Bibliometric Analysis of the Conceptual Model of Asnaf Entrepreneur Success - Efri Syamsul, Bahri; Juhary, Ali; Mohd Mizan, Mohammad Aslam (2022)
A specific study focusing on the success of asnāf entrepreneurs is currently very rare because zakāt distribution is still consumption dominant. The asnāf entrepreneur program is expected to be a sustainable solution for poverty alleviation and it deserves in-depth review. This study aims at building a conceptual model that determines the success of asnāf entrepreneurs. Literature research data were collected on publications produced between 2000 and 2020, sourced from Google Scholar, using published applications. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) and bibliometric approaches were used for data analysis. The results of the study led to development of a conceptual model for determining asnāf entrepreneur success, which includes six variables: characteristics, competency, intention, religiosity, resources, and opportunities. Asnāf entrepreneur success can be measured in four dimensions: life improvement, financial performance, non-financial performance, and maqāṣid sharī‘ah. Another important finding is that three theories, namely theory of planned behavior, giving back theory, and resource-based view, support the study. Two additional theories support the conceptual models, namely: human capital theory and theory of opportunity identification and development. Results of this study produced a conceptual model for determining success of asnaf entrepreneurs.